2015
DOI: 10.1097/hrp.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Parental and Child Characteristics Related to Early-Onset Disordered Eating

Abstract: Eating disorders are rare in children, but disordered eating is common. Understanding the phenomenology of disordered eating in childhood can aid prevention of full-blown eating disorders. The purpose of this review is to systematically extract and synthesize the evidence on parental and child characteristics related to early-onset disordered eating. Systematic searches were conducted in PubMED/MEDLINE, EMBASE, and PsycInfo using the following search terms: eating disorder, disordered eating, problem eating, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 69 publications
0
17
0
Order By: Relevance
“…Mothers tend to be more concerned about the nutritional status of their daughters, wishing them to be thinner. This may reflect the beauty standard imposed by the media and may lead to severe consequences, such as an increased prevalence of eating disorders [10,32,40]. Conversely, with regard to boys, it has been suggested that the greater trend of mothers to underestimate child’s nutritional status may be explained by the idealization of strong and robust bodies for male individuals, but additional studies are needed to evaluate these aspects [41].…”
Section: Discussionmentioning
confidence: 99%
“…Mothers tend to be more concerned about the nutritional status of their daughters, wishing them to be thinner. This may reflect the beauty standard imposed by the media and may lead to severe consequences, such as an increased prevalence of eating disorders [10,32,40]. Conversely, with regard to boys, it has been suggested that the greater trend of mothers to underestimate child’s nutritional status may be explained by the idealization of strong and robust bodies for male individuals, but additional studies are needed to evaluate these aspects [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some prospective studies have investigated effects of parent and family functioning in predicting later eating disorder onset with mixed results. For example, some evidence suggests that parental factors predict later eating pathology (Johnson, Cohen, Kasen, & Brook, ; Nicholls & Viner, ; Shoebridge & Gowers, ); however, reviews have not identified consistent patterns of risk associated with parenting styles or family interactions (Campbell & Peebles, ; Eisler, ; Larsen, Strandberg‐Larsen, Micali, & Andersen, ; le Grange, Lock, Loeb, & Nicholls, ; Strober & Humphrey, ; Yager, ). Indeed, greater family conflict, reduced parental alliance, and increased feelings of depression in families with a child suffering from AN might reflect an accommodation process in response to a severe and life‐threatening condition (Sim et al, ).…”
Section: Truth 2: Families Are Not To Blame and Can Be The Patients' mentioning
confidence: 99%
“… Typical patterns of family functioning or structure that give rise to eating disorders have not been identified. Families are not to blame and in most cases can be the patients' and providers' best allies in treatment. Reviews on family functioning in eating disorders point to the need for rigorous prospective designs to help understand how environmental variables, including family systems, may interact with biological risk (as discussed in Truths 7 and 8) to either heighten risk or buffer against the development of eating disorders (Larsen et al, ; Saltzman & Liechty, ). Eating disorders place stress on a family system, and future investigations that aim to reduce the burden on caregivers are necessary. Consideration of in‐home care may be a useful direction for services. Families represent an important base of support for those in recovery, and the effectiveness of FBT for adolescents highlights how parents and caregivers can be important allies in treatment.…”
Section: Truth 2: Families Are Not To Blame and Can Be The Patients' mentioning
confidence: 99%
“…The prevalence of self‐reported disordered eating at 7.2%, including weekly and monthly behaviours, is in accordance with findings from previous population‐based studies (Ricciardelli & McCabe, ). In general, the existing evidence indicates that females compared to males more often exhibiting eating psychopathology (Smink et al, ), but the evidence on sex differences in children and young adolescents is not consistent (Larsen et al, ). Our findings showed that any disordered eating was only slightly more frequent in girls than boys, but boys more frequently reported purging, whereas girls more frequently reported fasting, and binge eating.…”
Section: Discussionmentioning
confidence: 99%